Association between serum iron status and the risk of five bone and joint-related diseases: a Mendelian randomization analysis - Wang, Xiaolei; Qiu, Linjing; Yang, Zepei; Wu, Changjiang; Xie, Wenying; Zhang, Jing; Li, Wenhui; Li, Wangyang; Gao, Yanbin; Zhang, Taojing (Frontiers in Endocrinology, 2024)
Background: According to reports, iron status has been associated with the risk of bone and jointrelated diseases. However, the exact role of iron status in the development of these conditions remains uncertain.We obtained genetic data on iron status, specifically serum iron, ferritin, transferrin saturation (TSAT), and transferrin, as well as data on five common bone and joint-related diseases (osteoarthritis, osteoporosis, rheumatoid arthritis [RA], ankylosing spondylitis [AS], and gout) from independent genome-wide association studies involving individuals of European ancestry. Our primary approach for causal estimation utilized the inverse variance weighted (IVW) method. To ensure the reliability of our findings, we applied complementary sensitivity analysis and conducted reverse causal analysis.Result: Using the IVW method, we revealed a positive causal relationship between ferritin levels and the risk of osteoarthritis (OR [95% CI], 1.0114 [1.0021-1.0207]). Besides, we identified a protective causal relationship between serum iron levels and TSAT levels in the risk of RA (OR [95% CI] values of serum iron and TSAT were 0.9987 [0.9973-0.9999] and 0.9977 [0.9966-0.9987], respectively). Furthermore, we found a positive causal relationship between serum iron levels and the risk of AS (OR [95% CI], 1.0015 [1.0005-1.0026]). Regarding gout, both serum iron and TSAT showed a positive causal relationship (OR [95% CI] values of 1.